Menstrual Problems of Women in Bangladesh - Chowdhury, Sabiha (James P Grant School of Public Health, BRAC University, 2010)
Bangladeshi women suffer from menstrual problems such as dysmenorrhoea, menorrhagia, light and heavy bleeding during menstruation, and irregular period and are constantly worried if they menstrual flow is not a “normal” amount. They believe that a good menstrual flow is needed to stay healthy. If the flow decreases, they think that they’re must be “bad blood” trapped within their bodies, and if it stops altogether, they are concerned that they may have become infertile. Inability to conceive is viewed negatively in Bangladeshi society and women are subjected to psychological distress by society if they are perceived as infertile. Also, there are many social, cultural and religious taboos surrounding menstruation such as staying away from food such as fish, eggs, meat, sour fruits, etc during menstruation. Moreover, they are often advised to stay indoors as menstrual blood may attract evil spirits. Furthermore, these women also experience menstrual problems as side effects of contraceptives such as Norplant, IUD, and the pill, and sometimes discontinue its use as a result which may lead to unplanned pregnancies. Gynecological problems such as those related to menstruation are a major concern among Bangladeshi women, but social stigma and shame stand as a barrier against seeking proper healthcare. Often, they seek health advice from female relatives and unqualified health providers which in turn often leads to incorrect treatment and chronic menstrual related illnesses. Only a few studies have been carried out on menstrual problems in Bangladesh and most of them are either part of larger studies on side effects of contraceptives or a few small-scale exploratory studies. The aim of this literature review is to learn about local terminologies used to describe menstrual problems, to understand the practices and restrictions surrounding menstruation during adolescence, to learn about concerns surrounding infertility and its causes, to look at menstrual problems which result from use of contraceptives, and to examine patterns of health seeking behaviour of Bangladeshi women to treat their menstrual illnesses. This literature review was carried out by obtaining information from published reports, books and articles collected from local NGOs. Some information was also gathered from interviews with staff from local NGOs and gynaecologists from Bangladesh Railway Hospital. The review found that notions surrounding menstrual blood include perceptions that it is polluted and women should not serve food during this condition or touch anyone with an eye or skin infection as it may worsen their illness. Religious teaching also states that women are polluted during menstruation and cannot offer prayers in this state. Women tend to use local terminology to refer to menstrual problems such as kaler chut for dysmenorrhoea, humka batas for menorrhagia, and khum jhore if they get their periods twice or more a month. Perceived causes of menstrual related illnesses include evil spirits, lack of enough food, birth control pills, etc.